METHOXYCHLOR AND DIMETHOATE INDUCED CHANGES IN BIOCHEMICAL COMPONENTS OF THE HAEMOLYMPH AND FAT BODY OF THE LARVA OF RICE MOTH, CORCYRA CEPHALONICA STAINT. (LEPIDOPTERA : PYRALIDAE) - TIWARI, S. K.; BHATT, R. S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
Present study reveals that sublethal doses of methoxychlor and dimethoate caused a significantly dose dependent reduction in the levels of total protein, DNA, RNA, glycogen and in the activity of alkaline phosphatase and a similary dose dependent enhancement in the levels of total free amino acids, reducing sugar and in the activity of acid phosphatase in haemolymph and fat body of the larva of Corcyra cephalonica. The findings are discussed here in the light of influence of insecticidal agents on the basic extrinsic as well as intrinsic cellular mechanisms such as transport, synthesis, degradation and storage of the aforesaid biochemical constituents to prove the lethal action of the insecticide.